Transforming Character Education through KH. Zaini Mun’im’s Thought: Relevance of Nadhom Syu’abul Iman for Millennial Moral Development - Zaenol Fajri; Moh. Ashim (Journal of Islamic Education Research, 2026)
Contemporary character education models frequently emphasize cognitive and behavioral dimensions while paying limited attention to spiritual foundations. Addressing this gap, this study aims to examine KH. Zaini Mun'im's concept of character education, as articulated in Nadhom Syu'abul Iman, and its relevance to ethical challenges in the digital era. This study employed a qualitative library research design using Nadhom Syu'abul Iman as the primary source and scholarly publications on Islamic education, character education, and digital ethics as secondary sources. Data were collected through document analysis and analyzed using descriptive-analytical and hermeneutic approaches to interpret key concepts and reconstruct their educational implications. The findings reveal that KH. Zaini Mun'im conceptualizes character education as an integrated framework in which husnul khuluq serves as the central principle that connects spiritual consciousness, moral habituation, ethical communication, and social responsibility. Character is understood as the manifestation of faith through empathy, respect, accountability, self-control, and constructive social interaction. The study also demonstrates that the ethical values embedded in Nadhom Syu'abul Iman remain relevant for addressing digital communication ethics, cyber misconduct, and declining social empathy. The originality of this study lies in its reconstruction of KH. Zaini Mun'im's educational thought into a faith-based, transformative character education framework that integrates spiritual, moral, social, and digital dimensions. This study advances Islamic character education theory by providing a conceptually grounded, contextually relevant model for contemporary educational practice.